Analisis Pengelolaan Keuangan Desa Berdasarkan Permendagri Nomor 20 Tahun 2018 tentang Keuangan Desa - Masriyatul Mudrikah; Mellya Embun Baining; Atar Satria Fikri (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to determine the financial management process of Bumi Serdang village in the perspective of Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. This research is a type of descriptive research with a qualitative approach, namely the researcher conducted interviews with informants who were directly involved with activities in Bumi Serdang Village. Researchers used observation, interview and documentation data collection techniques as well as data analysis. The results of the research show that financial management in Bumi Serdang Village is as follows: (1) Financial management planning for Bumi Serdang village, Tungkal Ilir sub-district, Banyuasin Regency, namely the Village Secretary prepares a financial draft of village regulations regarding the Village APBDesa based on the RKPDesa. (2) Implementation of financial management in Bumi Serdang village, Tungkal Ilir sub-district, Banyuasin Regency, namely related to all village revenues and expenditures in the context of implementing village authority, carried out through the Village Cash Account. (3) Administration of the financial management of Bumi Serdang village, Tungkal Ilir District, Banyuasin Regency is carried out by Berdahara Village. (4) Reporting on the financial management of Bumi Serdang village, Tungkal Ilir sub-district, Banyuasin Regency, namely the Village Head submits a report on the realization of APBDesa implementation to the Banyuasin Regent in the form of a first semester report and a year-end semester report no later than the beginning of the year in accordance with the perspective of Permendagri No. 20 of 2018. (5 ) Accountability for the financial management of Bumi Serdang village, Tungkal Ilir sub-district, Banyuasin Regency. The Village Head submits an accountability report on the realization of APBDes implementation to the Regent of Banyuasin at the end of each fiscal year.